Wind Turbine and Photovoltaic Hybrid Generations under Extreme Operating Gust - Eid, Ahmad; Abdel-Akher, Mamdouh (Journal of Technology Innovations in Renewable Energy, 2014)
A micro-grid consisting of a 300kW wind turbine and a 40kW photovoltaic array is investigated under extreme operating gust (EOG) wind scenarios. The micro-grid is connected to the 380-V utility through a utility-side converter using natural-frame control, which provides a constant voltage of the DC link between the micro-grid and utility. The impact of the extreme gust wind variations on the micro-grid performance is studied for variable speed wind energy system equipped with a squirrel-cage induction generator. The Hurghada city, Red Sea, Egypt is taken as a case study for the wind speed profile. A detailed model of extreme gust-wind speed variation is implemented and simulated using PSIM commercial software package, based on climate characteristics of Hurghada city. The indirect rotor field oriented control (FOC) method is implemented to the generator-side converter to keep the system stable under the extreme gust wind conditions and to control the squirrel-cage induction generator (SCIG) speed for maximum power-point tracker (MPPT) regime. Power quality of the utility-side converter in terms of operation at different power factors, voltage value and THD are verified.